Histological and molecular diversity and heterogeneity of precancerous lesions associated with inflammatory bowel diseases. Issue 7 (4th December 2019) - Gui, Xianyong; Köbel, Martin; Ferraz, Jose GP; Iacucci, Marietta; Ghosh, Subrata; Liu, Shuhong; Ou, Young; Perizzolo, Marco; Winkfein, Robert J; Rambau, Peter; Demetrick, Douglas J
Abstract : Aims: Inflammatory bowel disease (IBD)-associated precancerous lesions may be adenomatous or non-adenomatous with various histomorphologies. We aim to validate the newly proposed classification, to explore the neoplastic nature of the non-adenomatous lesions and to elucidate the molecular mechanisms underlying the different histomorphologies. Methods: 44 background precursor lesions identified in 53 cases of surgically resected IBD-associated colorectal and ileal carcinomas were reviewed for the histomorphological features (classified into adenomatous, mucinous, sessile serrated adenoma (SSA)-like, traditional serrated adenoma-like, differentiated, eosinophilic and serrated not otherwise specified (NOS)) and analysed for a key panel of colonic cancer-related molecular markers. Results: Approximately 60% of the lesions were adenomatous, of which some had mixed serrated, mucinous or eosinophilic changes. The remaining non-adenomatous lesions, including all other types except SSA-like type, mostly showed mixed features and focal adenomatous dysplasia. KRAS mutation and p53 mutant-type expression were found in about half cases across all types, while PIK3CA mutation only in some of adenomatous and eosinophilic lesions and MLH1/PMS2 loss in a subset of adenomatous, mucinous and eosinophilic but not in differentiated and serrated lesions. SAT-B2 or PTEN loss and IMP3 overexpression were seen in a small subset of lesions. No BRAF, NRAS or EGFR gene mutation was detected in any type. Certain molecular-morphological correlations were demonstrated; however, no single or combined molecular alteration(s) was specific to any particular morphological type. Conclusions: IBD-associated precancerous lesions are heterogeneous both histologically and molecularly. True colitis-associated adenomatous lesions are unlikely conventional adenomas. Non-adenomatous lesions without frank cytologic dysplasia should also be regarded as neoplastic.